Exploring neuro-robotic rehabilitation: academic visit to the Advanced Medical and Dental Institute, Bertam / Rabiatul Adawiah Abdul Rahman - Abdul Rahman, Rabiatul Adawiah (UiTM Global @ Office of International Affairs, 2024)
BERTAM, PULAU PINANG 11 January 2024- In conjunction with the International Community Service between UiTM Pulau Pinang (UiTMCPP) Bertam Campus and Universitas Airlangga (UNAIR), Surabaya, Indonesia, the Physiotherapy Programme of the Faculty of Health Sciences, UiTMCPP Bertam Campus has organised an academic visit to the Physiotherapy Department and neuro-robotic clinic at Advanced Medical and Dental Institute (AMDI), Bertam. The delegation from UNAIR, consisting of 10 students and 2 lecturers from the Physiotherapy Programme, was accompanied by 3 lecturers from the Physiotherapy program, UiTM Bertam. The primary objective of the academic visit was to provide exposure to the current robotic technology utilized in the clinical setting in Malaysia. The application of robotics technology has expanded to provide both physical and mental assistance to humans. The field of rehabilitation robotics is experiencing growth, responding to the increasing demand for support in addressing neurological conditions and the health challenges associated with aging. The main goal of rehabilitation robotics is to enhance the rehabilitation process by integrating robotic technology, aiding physiotherapists in delivering optimal treatment to patients.